Induced spawning of curimatã‑pacu subjected to two hypophysation protocols - Santos, José Cláudio Epaminondas dos; Sato, Yoshimi; Santos, Athiê Jorge Guerra; Mendes, Paulo de Paula; Santiago, Kleber Biana; Luz, Ronald Kennedy (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to compare two hypophysation protocols in the spawning induction of curimatã‑pacu. The application of a single dose or two doses of crude carp pituitary extract was tested. That there was no significant difference among the protocols for the rate of females that have spawned, fertilization and deformed larvae. A single dose application resulted in higher degree‑hour values until the oocyte extrusion than two doses. The application of a single dose represented a lower consumption of water, energy, and handling time. A single dose protocol can be used as an alternative for inducing the curimatã‑pacu spawning.